Theoretical study of the plant residue movement along the needle of a rotating working organ. Issue 1 (September 2020) - Kem, A A; Shevchenko, A P; Begunov, M A; Koval, V S; Algazin, D N
Abstract: The article is devoted to the identification of dependences to determine the main rational constructive and technological parameters of the proposed rotating working organ.